Coherence and multimode correlations from vacuum fluctuations in a microwave superconducting cavity - Pasi Lähteenmäki (Nature Portfolio, 2016)
Vacuum fluctuations can produce observable phenomena which can potentially be harnessed, for example using the dynamical Casimir effect. Here, the authors show that, on the basis of the same effect, it is possible to establish distinct two-mode coherence correlations in a pumped microwave cavity owing to absence of which-way information.